If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5a + 10 = 3a Reorder the terms: 10 + 5a = 3a Solving 10 + 5a = 3a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-3a' to each side of the equation. 10 + 5a + -3a = 3a + -3a Combine like terms: 5a + -3a = 2a 10 + 2a = 3a + -3a Combine like terms: 3a + -3a = 0 10 + 2a = 0 Add '-10' to each side of the equation. 10 + -10 + 2a = 0 + -10 Combine like terms: 10 + -10 = 0 0 + 2a = 0 + -10 2a = 0 + -10 Combine like terms: 0 + -10 = -10 2a = -10 Divide each side by '2'. a = -5 Simplifying a = -5
| m/3+5=2 | | 69=-6n+9 | | 4(2x-3)=x-12+7k | | x+4+14+19=39 | | 2y+3x+x=840 | | 10+4x=5x+14 | | 13v=78 | | x-6=-5+8 | | 45-c=c+15 | | 45-c=c+30 | | 6(5+8r)-3r=6+3(8-3r) | | 0=x^2+x-7 | | n=-9+30 | | 23b=162 | | -28=2-3(4-3n) | | 5X^2+3X+8= | | -6v=-14 | | 8a^3=p^2 | | 11a=30+8a | | 6x-6-4x=6x-5 | | =-14-6v | | 9b=81 | | -x+4x=18 | | 2(2x-138)=x+24 | | 2x+3(.25x)=55 | | 4x+-8=18 | | 5f=-50 | | 4-6+5x= | | 4=-9 | | -7-(-8)=x | | 10.3x-32=-7x+28 | | (2x-(-4))(3x+(-2))=3-(5-3x)(2x+3) |